Preparation of S/N-codoped carbon nanosheets with tunable interlayer distance for high-rate sodium-ion batteries. Issue 19 (4th September 2017) - Zou, Guoqiang; Hou, Hongshuai; Zhao, Ganggang; Huang, Zhaodong; Ge, Peng; Ji, Xiaobo
Abstract : In this work, an ultra-thin sheet-like carbon with the co-doping of S and N prepared by a environmentally friendly one-pot method was firstly reported, delivering high-rate capability for SIBs. Abstract : The conventional strategies for obtaining S/N-codoped carbon materials suffer from a series of problems caused by their complicated experimental procedures. Here, S, N-codoped carbon nanosheets were firstly prepared by a solvent-free one-pot method, displaying an ultra-thin sheet-like structure, a tunable interlayer distance ranging from 0.37 nm to 0.41 nm, and a large surface area up to 809 m 2 g −1 . When they were used as an anode for sodium-ion batteries (SIBs), an outstanding sodium-ion storage performance of 380 mA h g −1 was acquired at 100 mA g −1, which can be attributed to the expanded interlayer distance caused by the introduction of the large covalent radius-sulfur. The initial coulombic efficiency improved to 60.9%, which may benefit from N-doping. Most importantly, an excellent rate capability of ∼178 mA h g −1 was observed at a current density of 5 A g −1 after 5000 cycles, which is among best of the state-of-the-art carbon-based SIBs. Interestingly, the morphology of the obtained carbon materials can be tuned from bulk to flake by adjusting the sulfur content or temperature. Given this, this work provides a new method to construct co-doped carbon (especially tri-doped and multi-doped carbon) and shows that the strategy of co-doping of heteroatoms can effectively optimize the nano/microstructure and enhance the rate capability of the carbon materials.